Plants of the Genus Terminalia: An Insight on Its Biological Potentials, Pre-Clinical and Clinical Studies - Das, Gitishree; Kim, Do-Yeong; Fan, Chen; Gutiérrez-Grijalva, Erick P.; Heredia, J. Basilio; Nissapatorn, Veeranoot; Mitsuwan, Watcharapong; Pereira, Maria Lourdes; Nawaz, Muhammad; Siyadatpanah, Abolghasem; Norouzi, Roghayeh; Sawicka, Barbara; et al. (Frontiers in Pharmacology, 2020)
The evaluation and confirmation of healing properties of several plant species of genus Terminalia based on their traditional uses and the clinical claims are of utmost importance. Genus Terminalia has received more attention to assess and validate the therapeutic potential and clinical approval due to its immense folk medicinal and traditional applications. Various species of Terminalia genus are used in the form of herbal medicine and formulations, in treatment of diseases, including headache, fever, pneumonia, flu, geriatric, cancer, to improve memory, abdominal and back pain, cough and cold, conjunctivitis, diarrhea, heart disorder, leprosy, sexually transmitted diseases, and urinary tract disorders. These are reported to possess numerous biological properties, counting: antibacterial, antifungal, anti-inflammatory, antiviral, antiretroviral, antioxidant, and antiparasitic. This current research review aims to update the detailed biological activities, pre-clinical and clinical studies of various extracts and secondary metabolites from several plant species under the genus Terminalia, along with information on the traditional uses and chemical composition to develop a promising strategy for their potential applications in the form of medicine or use in modern drug formulations for treating diseases like pneumonia, flu and other types of viral infections or controlling human contagions.